PENGARUH PENAMBAHAN BUBUR DAUN KEMANGI ( Ocimim basilicum L. ) TERHADAP KANDUNGAN GIZI KERUPUK SAGU - Hijra Wijaraya; Muhammad Wiharto Caronge; Muhammad Rais (Jurnal Pendidikan Teknologi Pertanian, 2019)
The purpose of this study was to determine the effect adding gruel of basil leave to the nutritional content of sago crackers. The experimental design used was a Completely Randomized Design (CRD) consisting of the concentration of the adding gruel of basil leave, namely: 0% (Control), 10%, 15%, and 20%. The parameters observed in this study were chemical analysis (water content, levels of provitamin A (β-carotene), phosphorus content, antioxidant content) and organoleptic value of sago crackers. The results showed that the concentration of adding gruel of basil leave affect water content, levels of provitamin A, especially β-carotene, phosphorus levels, and antioxidant levels of sago crackers. Likewise, on the results of acceptance or the level of panelist fondness. The best treatment, in terms of chemical analysis and organoleptic test, is sago crackers with the addition of 10% concentration of adding gruel of basil leave, with a value water content of 7.96%, provitamin A content (β-carotene) level of 1.96%, phosphorus content of 0.045%, and 3.98% antioxidant content, fondness value of color 3.23, fondness value of aroma 3.65, fondness value of flavour 3.87, and fondness value of texture 3.93